Synthesis, structure and properties of coordination polymers formed from bridging 4-hydroxybenzoic acid anions. Issue 10 (22nd February 2022) - Abrahams, Brendan F.; Commons, Christopher J.; Dharma, A. David; Hudson, Timothy A.; Robson, Richard; Sanchez Arlt, Robin W.; Stewart, Thomas C.; White, Keith F.
Abstract : The combination of 4-hydroxbenzoic acid with metal ions Li +, Mg 2+ and Cu 2+ leads to the formation of novel 2D and 3D networks. Abstract : The combination of 4-hydroxybenzoic acid (H2 hba) with Li +, Mg 2+ and Cu 2+ yields coordination polymers in which metal centres are bridged by an anion of the acid, either Hhba − or hba 2− . In the case of Li +, a 3D network of composition Li2 (hba)DMF was isolated in which parallel channels are occupied by coordinated DMF molecules. Mg 2+ combines with H2 hba to form a 2D square grid network with the formula Mg(Hhba)2 (H2 O)2 . The alignment of parallel sheets results in the formation of channels filled with 1, 4-dioxane molecules that hydrogen bond to coordinated water molecules. The compound Cu3 (hba)2 (OH)2 (1, 4-dioxane)1.5 ·0.5(1, 4-dioxane) is a complex 3D network formed from the combination of Cu 2+ with H2 hba under basic conditions. The crystal structure determination reveals bridging 1, 4-dioxane molecules. A reversible phase change occurs in the temperature range 200–220 K. The investigation highlights the key role of the solvent molecules in the structures of this series of compounds.